Regulatory Connections Between the Cyanobacterial Factor PipX and the Ribosome Assembly GTPase EngA - Jerez, Carmen; Salinas, Paloma; Llop, Antonio; Cantos, Raquel; Espinosa, Javier; Labella, Jose I.; Contreras, Asunción (Frontiers in Microbiology, 2021)
Cyanobacteria, phototrophic organisms performing oxygenic photosynthesis, must adapt their metabolic processes to important environmental challenges, like those imposed by the succession of days and nights. Not surprisingly, certain regulatory proteins are found exclusively in this phylum. One of these unique factors, PipX, provides a mechanistic link between signals of carbon/nitrogen and of energy, transduced by the signaling protein PII, and the control of gene expression by the global nitrogen regulator NtcA. PII, required for cell survival unless PipX is inactivated or down-regulated, functions by protein–protein interactions with transcriptional regulators, transporters, and enzymes. PipX also functions by protein–protein interactions and previous studies suggested the existence of additional interacting partners or included it into a relatively robust six-node synteny network with proteins apparently unrelated to the nitrogen regulation system. To investigate additional functions of PipX while providing a proof of concept for the recently developed cyanobacterial linkage network here we analysed physical and regulatory interactions between PipX and an intriguing component of the PipX synteny network, the essential ribosome-assembly GTPase EngA. The results provide additional insights into functions of cyanobacterial EngA and of PipX, showing that PipX interacts with the GD1 domain of EngA in a GDP-dependent manner and interferes with EngA functions in S. elongatus at low temperature, an environmentally relevant context. Therefore, this work expands the PipX interaction network and establish a connection between nitrogen regulation and the translation machinery. We discuss a regulatory model integrating previous information on PII-PipX with the results presented in this work.